An empirical analysis of the financial impact of supply chain management on small firms - James C. Brau; Stanley E. Fawcett; Ladd Morgan (The Journal of Entrepreneurial Finance and Business Ventures, 2007)
In this article we test the value proposition hypothesis of supply chain management (SCM) by examining survey results of 570 US managers. First, we find that large firms use SCM initiatives significantly more than small firms. Second, in univariate and multivariate tests, we find that SCM leads to significant improvements in asset utilization, revenue generation, and competitive performance, regardless of firm size. These two major findings suggest that managers at small firms that are not actively engaged in SCM should reevaluate their opportunity to capture the competitive benefits of SCM that many large firms currently enjoy.
Keywords: 650